An online continuous professional development programme on literature pedagogy for the teaching of Mahua literature in Malaysia - Kuek, Florence; Ng, Soo Boon; Ng, Yean Leng; Chai, Siaw Ling; Fan, Pik Shy (Penerbit Universiti Kebangsaan Malaysia, 2021)
Chinese Language is a subject offered in both Malaysian Primary and Secondary schools. Given that literary appreciation forms a part of the curriculum content, the Chinese textbooks used in schools have incorporated a good selection of localised literature, known as Malaysian Chinese (Mahua) literature. However, feedback from language teachers revealed that there was a lack of reference resources on Mahua literature, causing them to request for more support in this regard (Malaysia Sin Chew Daily, 6 June 2020). Their lack of familiarity with Mahua literature warrants a continuous professional development (CPD) programme. In response, the Chinese Studies Department of University of Malaya and the Writers’ Association of the Chinese Medium of Malaysia jointly developed and implemented a 10-week online intervention course for Chinese Language teachers. The observations of the researchers yielded a pedagogical framework of Mahua literature encompassing four aspects, namely, (a) linguistic features; (b) imagery or object representation; (c) “pathos” or the affective aspect; and (d) “logos” or the motive of the text. In brief, this pedagogical framework can be termed as the “Language-Representation-Affect-Motive” (LRAM) framework. It is significant that Chinese Language teachers would view Mahua literature as being more challenging than Chinese literature from the Mainland to teach and prepare lessons for. Nevertheless, the research findings have, to a certain extent, affirmed that the LRAM framework was effective in addressing the felt needs of these teachers. The research also revealed that the LRAM was well-accepted as a feasible pedagogy of literature in assisting both novice and experienced Chinese Language teachers to dive deeper into Mahua literature. The feedback and reflections from the interviewees discussed reflect the participants’ opinions concerning the weightage of localised content in Chinese textbooks, as well as the literary value of Mahua literature. All in all, this study applies a socio-ecological approach in examining the LRAM literature pedagogy implemented in an online CPD programme on Mahua literature.